2019
DOI: 10.1002/ptr.6281
|View full text |Cite
|
Sign up to set email alerts
|

The nitrergic neurotransmission contributes to the anxiolytic‐like effect of Citrus sinensis essential oil in animal models

Abstract: Citrus fragrances have been used in aromatherapy for the treatment of anxiety, and the essential oil of Citrus sinensis (sweet orange) has shown promising results, although its mechanism of action was not known. The objective of this study was to evaluate the involvement of nitric oxide (NO) neurotransmission in the anxiolytic-like effect of C. sinensis essential oil. Swiss male mice were submitted to 15 min of C. sinensis essential oil inhalation (1%, 2.5%, 5%, and 10%) and tested in the marble-burying test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…In another study with Swiss male mice tests, the essential oil of C. sinensis exerted an anxiolytic-like effect without altering locomotor activity. The researchers found that pre-treatment with Larginine prevented this anxiolytic-like effect in animals and concluded that nitrergic neurotransmission plays a relevant role in the anxiolytic effect of C. sinensis essential oil (Hocayen et al, 2019). A clinical trial tested the effects of orange essential oil compared to fluoxetine in 150 individuals with major depressive disorder -evaluated using the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV).…”
Section: Sweet Orange (Citrus Sinensis)mentioning
confidence: 99%
“…In another study with Swiss male mice tests, the essential oil of C. sinensis exerted an anxiolytic-like effect without altering locomotor activity. The researchers found that pre-treatment with Larginine prevented this anxiolytic-like effect in animals and concluded that nitrergic neurotransmission plays a relevant role in the anxiolytic effect of C. sinensis essential oil (Hocayen et al, 2019). A clinical trial tested the effects of orange essential oil compared to fluoxetine in 150 individuals with major depressive disorder -evaluated using the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV).…”
Section: Sweet Orange (Citrus Sinensis)mentioning
confidence: 99%
“…Due to the growing problem of drug resistance, new therapeutic solutions are sought for, especially those of natural origin. Essential oils, due to their anti-bacterial, anti-fungal, antiinflammatory and immunostimulatory properties, constitute interesting research material in the fight against mould [14][15][16][17][18].…”
Section: Introduction and Objectivementioning
confidence: 99%
“…Sweet orange (Orange peel) and Agarwood are classic Herb pairs, which have the effect of relieving qi stagnancy in liver and resolving stagnation for tranquilization. From the perspective of Western medicine, Lavender [25, 26] has sedative-hypnotic effects and anti-anxiety effects, Sandalwood [27] and Agarwood [28] have sedative-hypnotic effects, Sweet orange [29], Rose [30], Frankincense [31] and Orange Blossom all have anti-depression effects. In this study, the Lavender essential oil, a commonly used in the treatment of insomnia, was combined with the Qi-regulating drugs’ essential oil to prepare the Compound Anshen essential oil and its effect on sedative and hypnotic effects with inhalation administration were studied.…”
Section: Introductionmentioning
confidence: 99%